Analysis of the Role of Management Information Systems (MIS) as a Pillar of Strategic Decision Making in the Digital Era to Optimize Reporting Accountability in Educational Institutions - Ahmad Nursodiq; Ariful Farhan; Alifia Alifia; Krisna Wahyu Setiawan; M Yudi Mardiyansyah (Jurnal Multidisiplin Sahombu, 2026)
The development of digital technology requires educational institutions to manage data and information more effectively to support strategic decision-making and improve reporting accountability. Management Information Systems (MIS) are a crucial instrument because they can integrate data in a structured, accurate, and timely manner, thus supporting data-driven decision-making. This article aims to analyze the role of MIS in strategic decision-making in the digital era, identify its contribution to optimizing reporting accountability in educational institutions, and explain the factors influencing the success of MIS implementation in digital reporting management. The research method used is a qualitative approach through a literature review, reviewing various books, journal articles, and relevant scientific sources. The results of the study indicate that MIS plays a significant role in providing objective information, supporting data-driven decision-making, and increasing transparency and accountability in academic and financial reporting. The success of MIS implementation is greatly influenced by the competence of human resources, the readiness of technological infrastructure, and the support of leadership and organizational policies. Thus, MIS can be viewed as a strategic pillar in strengthening the governance of educational institutions that is professional, transparent, and adaptive to the demands of the digital era.